ОСНОВНІ ХАРАКТЕРИСТИКИ СУТНОСТІ ТА ЗМІСТУ ПОНЯТТЯ ІНДИВІДУАЛЬНОЇ ОСВІТНЬОЇ ТРАЄКТОРІЇ СТУДЕНТА В ПРОЦЕСІ ПРОФЕСІЙНОЇ ПІДГОТОВКИ (World Science, 2019)
The author provided the theoretical grounding of the essential characteristics of the concept of “individual educational trajectory”. Based on the logem of the system of the methodological approaches (holistic- emergent, humanitarian, axiological, trans-communicative, personal- activity, praxeological, projected, competent, creative-acmeological), she formulated the definition of the individual educational trajectories of the future teachers of the music art and she outlined briefly the structural content of the research question which is represented with two blocks: personal potential (motivational-value, personal-experience, orientation- cognitive, communicative reflexive and regulatory components) and its realization in the educational activities.